Monitoring the Site-Specific Solid-State NMR Data in Oligopeptides - Czernek, Jiří; Brus, Jiří (International journal of molecular sciences, 2020)
Reliable values of the solid-state NMR (SSNMR) parameters together with precise structural data specific for a given amino acid site in an oligopeptide are needed for the proper interpretation of measurements aiming at an understanding of oligopeptides' function. The periodic density functional theory (DFT)-based computations of geometries and SSNMR chemical shielding tensors (CSTs) of solids are shown to be accurate enough to support the SSNMR investigations of suitably chosen models of oriented samples of oligopeptides. This finding is based on a thorough comparison between the DFT and experimental data for a set of tripeptides with both 13Cα and 15Namid CSTs available from the single-crystal SSNMR measurements and covering the three most common secondary structural elements of polypeptides. Thus, the ground is laid for a quantitative description of local spectral parameters of crystalline oligopeptides, as demonstrated for the backbone 15Namid nuclei of samarosporin I, which is a pentadecapeptide (composed of five classical and ten nonproteinogenic amino acids) featuring a strong antimicrobial activity.
Keywords: Oligopeptides; magnetická rezonanční spektroskopie; peptidy; Amino Acids; Magnetic Resonance Spectroscopy; izotopové značení; oligopeptidy; aminokyseliny; Isotope Labeling; Peptides